Evaluation of Antifungal Efficacy of Selected Microorganisms Against Apple Rot Pathogens - Neelam Kumari; J. N. Sharma; Deepika Singh (International Journal of Economic Plants)
Biological control of post harvest pathogens of fruits and vegetables is an effective alternative to chemical based treatments because of its minimal impact on the environment and human health. The antifungal efficiency of antagonistic microorganisms occurring naturally on apple fruit surface (Trichoderma viride, T. hamatum, T. harzianum, Bacillus subtilis, Pseudomonas fluorescens and one yeast isolate) against post harvest pathogens of apple (Alternaria alternata, Monilinia fructigena, Trichothecium roseum, Aspergillus niger, Penicillium expansum) was evaluated both under in vitro and in vivo conditions. Overall maximum growth inhibition of all the test fungi (71.97%) was reported with T. hamatum followed by the yeast isolate (66.63%), B. subtilis (64.98%) and T. harzianum (62.43%).